Expression of Membrane-Bound CC Chemokine Ligand 20 on Follicular T Helper Cells in T–B-Cell Conjugates - Lee, Adrian Y. S.; Reimer, Dorothea; Zehrer, Annette; Lu, Ming; Mielenz, Dirk; Körner, Heinrich (Frontiers in Immunology, 2017)
The CC chemokine receptor 6 (CCR6) and its sole chemokine ligand CC chemokine ligand 20 (CCL20) display an emerging role in the coordination of humoral immune responses. Recent studies demonstrate a role of this chemokine axis in the migration of B cells to key immunological sites during an immune response, and facilitating the generation of high-quality antibodies. Very little, however, is known about CCL20 and its role in these functions. We undertook a preliminary investigation into the expression and function of CCL20 and demonstrate its well-noted up-regulation in the spleen during immunisation. Furthermore, we show that most follicular T helper (Tfh) cells can be CCR6+ and can produce CCL20. Surprisingly, CCL20 can not only be found in the cytoplasm but also on the surface of these cells and their precursors. Analysis of T-B-cell conjugates revealed that mature Tfh cells, but not their precursors, are highly enriched in the conjugates. Further functional studies are needed to unravel the precise role of CCL20 in coordinating T and B cell interactions during the humoral immune response.